Exploring Notions of Environmental and Ecological Justice Among Settler Protesters Opposed to the Trans Mountain Expansion Project - Strumos, Lauren Taylor (Université d'Ottawa / University of Ottawa, 2025)
The Trans Mountain Expansion project entailed the construction of a new interprovincial oil pipeline in western Canada that terminates at Burrard Inlet in the Metro Vancouver region of British Columbia. This thesis focuses on settler opposition to the pipeline project as an entry point to explore how religion and nonreligion shape terrestrial relations amidst the planetary crisis. How do religious and nonreligious individuals understand their moral relations with those who share their dwelling place? The field of religion and ecology emerged in the mid-1990s and has since highlighted the role of religion in fostering moral beliefs and practices in a more-than-human world. Nonreligion is a relatively recent area of study and research on the intersections of nonreligion and ecology remains scarce. This gap is noteworthy given the rise of individuals who identify with no religion in and beyond Canada, especially during a time of heightened awareness for the climate and ecological crises. Contributing empirical research on religion, nonreligion and ecology, this thesis presents data from semi-structured interviews with (non)religious individuals actively opposed to the pipeline project. The conceptual framework is drawn from theories of environmental justice and ecological justice. The following question guided the analysis: to what extent do the perspectives of (non)religious individuals engaged in activism against the Trans Mountain Expansion project represent principles of environmental and ecological justice? The analysis revealed that participant views on the harms of the pipeline project, and their motivations for actively opposing it, resonated with climate justice for younger and future humans; procedural justice for Indigenous nations who did not consent to pipeline construction on their territories; and ecological justice for nonhumans directly harmed or threatened by pipeline construction. These notions of justice were evident to varying degrees in the narratives of both religious and nonreligious participants. The ways in which they manifested were influenced by participants' lifestances, which includes their nonreligious, spiritual and religious identities as well as a social imaginary shaped by Christianity.
Keywords: Trans Mountain; Sociology of Religion; Nonreligion; Religion and Ecology; Environmental Justice; Climate Justice; Ecological Justice; Lifestances; Stewardship